Strategia wzrostu konkurencyjności Unii Europejskiej w warunkach rozszerzenia w 2004 r. oraz globalizacji - Puślecki, Zdzisław (Strategy of the European Union Increase of Competitiveness in the Conditions of the Enlargement in 2004 and Globalization, 2005)
The most important long-term social-economic program of the European Union are the cohesion policy and structural policy. Now especially role in this program play the Lisbon strategy accepted al the meeting of the European Council in March 2000. It is aimed at making the European Union by the year 2010 the most competitive and dynamic, knowledge-driven economy in the whole world, capable of stable, continuous development, of creating bigger numbers of better jobs and distinguished by a bigger social cohesion. It should be also pointed out that lower so far, when compared with that of the USA, level of the commercialization of research is a permanent feature of Europe; in other words, practical implementation of knowledge and of the research-development potential, which in certain fields reaches the highest, world levels, is much inferior. Market has not reached this area of activity in a satisfying degree yet, and the ties between the institutions of higher learning and the real social-economic life are relatively weak. In the face of the increase competitive strategy of the EU any efforts to think and act alone - within national policies - cannot bring about excellent and long lasting results. It will soon prove necessary to take advantage of that huge developmental reserve in the shape of a uniform internal market. The economic situation will stimulate the political integration. At the same time, not only governments, but whole societies will exert the pressure to introduce reforms in those countries that slow down progress. Therefore, the first decade after the year 2000 will witness deep transformations in Western Europe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 291-301